Pengamanan Pintu Ruangan Menggunakan Arduino Mega 2560, MQ-2, DHT-11 Berbasis Android - Siswanto Siswanto; M Anif; Dwi Nur Hayati; Yuhefizar Yuhefizar (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
In the era of technological advancements, security systems are not only required to provide safe conditions but also provide easy access, monitors and remote control. Room insecurity such as theft or fire cases can occur especially in rooms that are not equipped with security systems and special safeguards. Based on this, it is necessary to develop a security system that can be accessed and monitored remotely and provides early warning of early indications of danger through a smartphone. System development is done through the stages of making software and hardware. The hardware consists of Arduino Mega 2560 to regulate the system, MySQL Server Database, CC3000 Wi-Fi Shield as a communication device between Arduino and the server, Limit Switch to detect forced push on the door, MQ-2 measures the presence of indoor gas leak, sensor DHT-11 to measure room temperature, the camera is VC0706 to capture images in the door area. Android application as a system interface to change key status and monitor the condition of the room. A warning notification of the gas leak danger indication is sent to the user's smartphone by displaying the gas content value. A warning message has a forced push on the door equipped with a feature to display the camera capture results. The final result of this research is that a room security system has been successfully established where door lock access and room monitoring can be done through an android application installed on a smartphone. The system can provide hazard warning messages properly.